PENGARUH ENTERPRISE RISK MANAGEMENT & INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN YANG TERCANTUM DALAM INDEKS LQ45 BEI - Herawati, Stevani Wahyu; Riswandari, Ernie (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract” The Purpose of this study to determine the effect of enterprise risk management and intellectual capital on the firm value. The value of the firm is reflected in the stock price but in fact the stock price always fluctuates up and down which is unstable, including in companies that are indexed LQ45.Enterprise Risk Management measured by Enterprise Risk Disclosure Index (ERMDI),Intellectual Capital by Valued Added Human Capital (VAHU), Value Added Capital Employed (VACA),Structural Capital Value Added (STVA), and Company Value measured by Tobin's Q. This study used secondary data obtained from the corporate official website and Indonesia Stock Exchange ( www.idx.co.id ). The sample used as many 25 companies were listed at index LQ45 IDX which selectedwith use purposive sampling method. Method of analysis used is descriptive statistic test, the classical assumption test and testing of hypothesis using SPSS version 25. Based on the result of concluding that ERM,VAHU, and VACA were Partially positive effects on the Company Value and STVA were partially have no effect on the Company Value. ERM, VAHU, VACA, STVA were Simultaneously positif effect on the Company Value. Keywords: Company Value; ERM; IC; VAIC; VAHU; VACA; STVA